2020
DOI: 10.21462/ijefl.v5i2.249
|View full text |Cite
|
Sign up to set email alerts
|

Code Mixing in College Students’ Presentation: A Case in an Intercultural Communication Class

Abstract: Studying the second language (L2) was happens around the world because of some reasons such as education. Studying another language can be important in intellectual human activities after studying first language (L1). However using L2 is quite hard because some of them use L2 just for some their activities, not for the whole of their activities, such as students who use English only when studying English subject only or on the contrary. Nowadays, some people use two language at the same time, which is called c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In relation to this point, there were several researchers who had conducted previous studies about code mixing focused on social life and media (Piantari et al, 2011;Samhan, 2017;and Syafaat & Setiawan, 2019). The research on code mixing is not only on social media and in society or community, but also in classroom interaction (Moetia et al, (2018;Rini & Rustandi, 2018;Maulidar et al, 2020;Rahmat, 2020;Rinawati et al, 2020;and Helmie et al, 2020). Moetia et al, (2018) Code Mixing and Code Switching in the Classroom Interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to this point, there were several researchers who had conducted previous studies about code mixing focused on social life and media (Piantari et al, 2011;Samhan, 2017;and Syafaat & Setiawan, 2019). The research on code mixing is not only on social media and in society or community, but also in classroom interaction (Moetia et al, (2018;Rini & Rustandi, 2018;Maulidar et al, 2020;Rahmat, 2020;Rinawati et al, 2020;and Helmie et al, 2020). Moetia et al, (2018) Code Mixing and Code Switching in the Classroom Interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rinawati et al, (2020) conducted research on A Code-Mixing Analysis on EFL Students' Casual Conversations at School, and the result showed that students did code mixing in their communication with their friends at school, they are frequently use phrase insertion and word insertion in communication, rather than hybrid, repetition word, idioms and clauses insertion. The last previous studies based on Helmie et al, (2020), conducted research on Code Mixing in College Students' Presentation: A Case in an Intercultural Communication Class, based on Hoffman's theory. The result showed that the languages that dominate in the presentation are English and Bahasa Indonesia equally.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, individuals with the ability to speak more than one language engage in constant code-switching and code-mixing during conversations. Helmie, Halimah, and Hasanah (2020) assert that bilingualism and multilingualism have become prevalent in contemporary society, leading those raised in a unicultural and monolingual environment to perceive these phenomena as unusual. Malaysia's education system underscores the importance of learning several languages, including English and Arabic, starting from the age of 6.…”
Section: Introductionmentioning
confidence: 99%
“…Code switching and mixing indicate that the speaker lacks fluency (Bonyadi, Kalvanagh, and Bonyadi 2021), lacks credibility and demonstrates ineptitude (Horasan 2014), and does not reach the desired target language (Wang &Wu 2016). This idea arises because excessive switching and mixing codes can affect students' proficiency in English from classes that always use full English (Helmie, Halimah, and Hasanah, 2020). Switching and mixing codes are feared to have many disadvantages and can affect students' communication.…”
Section: Introductionmentioning
confidence: 99%